Effect of nitrogen supply on nitrogen and carbohydrate constituent accumulation in rhizomes and storage roots of Curcuma alismatifolia Gagnep. - Norikuni Ohtake (2018)
Curcuma (Curcuma alismatifolia cv. Gagnep.), a tropical flowering plant known as "Siam tulip", were cultivated in a pot with vermiculite and supplied with different levels of nitrogen (N). Rhizomes with storage roots were harvested at 215 days after planting. Results indicated that a high level of N supply increased flower numbers and promoted continuous new rhizome formation, but storage root growth was depressed. The N supply to the plants increased the N concentrations both in the rhizomes and in the storage roots. The predominant nitrogenous compounds related to total N increase were proteins in the rhizomes. The N of the insoluble fraction of 80% ethanol or the N of the soluble fraction of 10% trichloroacetic acid was the predominant fraction of N that accumulated in the storage roots. A lack of N supply increased the starch concentration both in the rhizomes and in the storage roots. These results suggested that a high level of N supply to the curcuma plant increased new rhizome formation because of increased flower numbers, but depressed new storage root formation because of reduced starch accumulation. © 2006 Japanese Society of Soil Science and Plant Nutrition.